MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA MELALUI MODEL DISCOVERY LEARNING DENGAN THINK-PAIR-SHARE PADA SISWA - Lena Rosdiana Pangaribuan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Mathematics is one of the subjects that plays a very important role in the development of science and technology. Therefore, the government is always trying to make the quality of mathematics education better from time to time. After conducting classroom action research, based on the results of observations and reflections, it can be concluded that: The Discovery Learning Learning Model with Think-Pair-Share can improve students' mathematics learning activities. Improved class students' mathematics learning activities by applying this learning model from cycle I to cycle II. In the Think-Pair-Share implementation, students are given a sheet containing a summary of the material and questions regarding the material to be taught. Question sheets are arranged in the form of Student Activity Sheets (LKS). LKS are given after the process of observing and the subject matter is arranged systematically from easy questions to difficult questions. Students are given the opportunity to answer the question as best they can within the allotted time limit. The concept discovery process is carried out in groups (pairs), students have individual and group responsibilities and have the same opportunity to succeed. Students who have higher mathematical abilities can help students (partners) with lower abilities in learning mathematics.Keywords: Improve, Learning Activities, Discovery Learning Model, Think-Pair-Share.